The influence of formal education, years of service and team meetings on the quality of interaction in Austrian centre-based settings for children under 3 years - Claudia Geißler; Tanja Sonnleithner; Mailina Petritsch; Catherine Walter-Laager (Journal of Early Childhood Education Research, 2022)
Previous studies have reviewed positive correlations between the formal education levels of educators in Early Childhood Education and Care (ECEC) centres and the quality of interactions, but the findings have not been consistent (Early et al., 2007; Manning et al., 2017). Moreover, informal learning processes seem to be important too (Pianta et al., 2016). The present paper addresses this and explores how education levels of ECEC staff, years of service, and the frequency of team meetings relate to the quality of interactions in Austrian centre-based settings for children under 3 years. The interaction quality was measured among early childhood educators and assistants (N = 116) using the Graz Scale of Interaction Quality for Children between 0 and 3 years (GrazIAS 0-3) (Walter-Laager, Flöter et al., 2019). The results of multiple regression models indicate that the frequency of team meetings strongly positively correlates with both the subscales of interaction quality, 'ensure relationships and wellbeing' and 'support learning'. Further, the level of education of the ECEC staff and their years of service positively correlate with the subscale 'support learning' with low-to-medium effect sizes. The findings also suggest that team meetings might be important for increasing the quality of interactions at ECEC centres.